If in Later Years - Moore, Ronald E., 1939- (Book collections on Project MUSE., 2014)
If in Later Years is filled with poems of depth and insight that provoke, engage, surprise, and astound. Reading Ron Moore's second collection of poetry takes readers on journeys around the world and back through the ages of time. Each poem is written with great insight, learning, and craft, and each invites multiple readings and reflection. From a Tibetan monk sitting in silence and contemplating the atom to a love affair with Buenos Aires, Moore takes his readers on journeys that are both personal and profound. While each poem has its own voice and beauty, Moore shapes all of them with lyrica.